The Mindful Interactions (MI) tool : promoting student mental health in tertiary education. - Stephenson, Elspeth; Yost, Helen (Journal of University Teaching & Learning Practice v.20 n.7 https://doi.org/10.53761/1.20.7.03, 2023)
This conceptual paper introduces the Mindful Interactions (MI) tool designed to enable university teaching academics to promote student mental health and in so doing, impact positively on academic outcomes. The MI tool is comprised of three elements: understandings to provide theoretical guidance which inform pedagogy, practices to provide strategies for translating theory into practice, and guiding principles which provide a catalyst for critical reflexion, challenge existing beliefs, and create a shared vision from which to work. Relationships are at its core, acknowledging that university students report teacher-student relationships as key to their mental health. Issues related to university student mental health, of which psychological distress is an important component, have been well documented and exacerbated since the onset of COVID-19, increasing demands on universities to meet student mental health needs. It is contended in this paper that understanding the causes of psychological distress, particularly in relation to Adverse Childhood Experiences, offers an alternative lens through which to view student mental health. This lens suggests additional ways of thinking about how university teaching academics and universities might proactively respond to student mental health needs. Cultural Historical Activity Theory informed the theoretical framework for the study, whilst two 'approaches' (the 'Three Pillars of Trauma-informed Care' and 'Trust Based Relational Intervention') along with associated trauma literature underpinned the development of the MI tool. [Author abstract]